Optimal design of acoustic metamaterials for noise suppression by the frequency division in military equipment - Shaohua Bi; Fei Yang; Xinmin Shen; Wenqiang Peng; Xiaocui Yang; Qin Yin; Xiaonan Zhang; Heng Zhang; Dong Wang; Jingguo Chen; Zhiming Li (AIP Advances)
This paper presents a multi-Helmholtz unit series–parallel acoustic metamaterial with a segmented noise control effect designed by taking advantage of the adjustable frequency band of an acoustic metamaterial, aiming to change the main noise spectrum characteristics under different driving conditions of military equipment such as tanks. Based on the transfer matrix method, a theoretical model that can predict the acoustic characteristics of a hybrid structure with multiple Helmholtz resonator (HR) units is established, and its feasibility is verified through finite element simulations and experiments. By combining particle swarm optimization with finite element simulation, the suboptimal average sound absorption coefficient (αavg) of ten populations was 0.52, 0.54, 0.54, and 0.44, respectively, after iterating for 50 generations. The results demonstrate that the αavg of the four groups of HRs in series with three layers reaches 0.79, 0.62, and 0.66, respectively, at the frequency bands of 205–285, 540–720, and 940–1130 Hz, and the overall thickness of the longest part is 88 mm. Low-frequency noise at approximately λ/18 can be controlled. The HR obtained by means of the first series and then parallel can achieve accurate sound absorption for specific frequency bands and can reduce its volume by removing redundant absorption bands. The findings of this study provide an effective noise-control scheme for changing the noise environment in military equipment.